Practice Patterns after the Therapeutic Hypothermia After Pediatric Cardiac Arrest Out-of-Hospital Trial: A Survey of Pediatric Critical Care Physicians - Gildea, Marianne R.; Moler, Frank W.; Page, Kent; Pemberton, Victoria L.; Holubkov, Richard; Nadkarni, Vinay M.; Dean, J. Michael; Olson, Lenora M. (Journal of Pediatric Intensive Care, 2019)
The Therapeutic Hypothermia After Pediatric Cardiac Arrest Out-of-Hospital (THAPCA-OH) Trial showed therapeutic hypothermia, versus normothermia, did not significantly improve 1-year survival with good neurobehavioral outcome. Our survey of pediatric critical care physicians, designed to assess the use of targeted temperature management (TTM) after publication of the main THAPCA-OH Trial results, found most respondents were aware of trial results, and over 90% agreed THAPCA-OH was well-designed with important clinical outcomes. While most respondents reported TTM usage consistent with THAPCA-OH results in different patient scenarios, 15% did not select TTM for fever management. Since trials prior to THAPCA-OH established that fever is harmful following brain injury, the continued incomplete adoption of TTM warrants further research on challenges and facilitators to the adoption of clinical trial findings.
Keywords: targeted temperature management; THAPCA-OH; survey